Wu-Mei-Wan enhances brown adipose tissue function and white adipose browning in obese mice via upregulation of HSF1 - Shen Chen; Kexin Nie; Hongzhan Wang; Yang Gao; Xinyue Jiang; Hao Su; Zhi Wang; Yueheng Tang; Fuer Lu; Hui Dong; Jingbin Li (Chinese Medicine)
Abstract Background This research aims to explore the anti-obesity potential of Wu-Mei-Wan (WMW), particularly its effects on adipose tissue regulation in obese mice induced by a high-fat diet (HFD). The study focuses on understanding the role of heat shock factor 1 (HSF1) in mediating these effects. Methods HFD-induced obese mice were treated with WMW. Body weight, food intake, and histopathological analysis of adipose tissue were conducted. Brown adipose tissue (BAT) activity was evaluated using Positron Emission Tomography, and ultrastructural changes were examined via transmission electron microscopy. Proteomic analysis identified targets of WMW in obesity treatment. HSF1 expression was inhibited to confirm its role. Molecular docking studied interactions between WMW and HSF1. Short-chain fatty acids (SCFAs) in the intestines were measured to determine if WMW’s effects on HSF1 are mediated through SCFAs. Protein expression was assessed using western blot, immunohistochemistry, immunofluorescence and RT-qPCR were employed to detect the mRNA levels. Statistical analyses included t-tests, ANOVA, and non-parametric tests like the Mann–Whitney U test or Kruskal–Wallis test. Results WMW significantly mitigates the adverse effects of a HFD on body weight and glucose metabolism in obese mice. Both low-dose WMW and high-dose WMW treatments led to reduced weight gain and improved glucose tolerance, with low-dose WMW showing more pronounced effects. WMW also reversed structural damage in BAT, enhancing mitochondrial integrity and thermogenic function, particularly at the low dose. Additionally, WMW treatment promoted the browning of WAT, evidenced by increased expression of key thermogenic proteins such as UCP1 and PGC-1α. The increase in HSF1 expression in both BAT and WAT, observed with WMW treatment, was crucial for these beneficial effects, as inhibition of HSF1 negated the positive outcomes. Furthermore, WMW treatment led to elevated levels of short-chain fatty acids SCFAs in the intestines, which are associated with increased HSF1 expression. Conclusions WMW represents a potent therapeutic strategy for obesity, promoting metabolic health and beneficial modulation of adipose tissue through an HSF1-dependent pathway.